2000
DOI: 10.1007/s101510050049
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal function and clinical outcome after open and closed haemorrhoidectomy, with and without internal sphincterotomy. A prospective study

Abstract: To compare the clinical and functional results after open and closed haemorrhoidectomy with or without internal sphincterotomy, 55 patients were randomised into

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…Postoperative pain was acceptable, being similar to that reported after conventional operations [3]. One may argue that stitching the distal perianal skin might increase pain, but the method is used for the management of postfistulotomy wounds and has not been followed by a more painful postoperative course in a controlled prospective study (unpublished observations).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Postoperative pain was acceptable, being similar to that reported after conventional operations [3]. One may argue that stitching the distal perianal skin might increase pain, but the method is used for the management of postfistulotomy wounds and has not been followed by a more painful postoperative course in a controlled prospective study (unpublished observations).…”
Section: Discussionsupporting
confidence: 71%
“…The aims of semiclosed hemorrhoidectomy are: (i) to avoid any suture tension in the anal canal and subsequently to decrease the risk of dehiscence, which has been reported after the Ferguson operation [2], (ii) to minimize the risk of postoperative bleeding, which may occur after both open and closed hemorrhoidectomies [3], and (iii) to leave a small wound in the anal canal, thus decreasing the healing time and allowing an earlier return to work [4].…”
Section: Discussionmentioning
confidence: 99%
“…No such case was found in this study, as the disorder itself is not common in India. As the fibers of the internal sphincter were severed in the surgical procedures, no additional sphincterotomy or anal stretch was necessary to relieve the anal spasm, as reported by others in association with hemorrhoidectomy [22].…”
Section: Discussionmentioning
confidence: 71%
“…Six studies15, 27, 44, 66, 67, 75 compared conventional closed haemorrhoidectomy with open haemorrhoidectomy ( Table S2 , supporting information). Three27, 67, 75 of the six studies observed significantly lower pain scores with conventional closed versus open haemorrhoidectomy ( P < 0·01 to P < 0·05).…”
Section: Resultsmentioning
confidence: 99%